2018
DOI: 10.1089/zeb.2017.1519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oil from Thymus vulgaris on Viability and Inflammation in Zebrafish Embryos

Abstract: Innate immunity provides the initial response against pathogens and includes the inflammatory response. Regulation of the initiation and duration of neutrophil and mononuclear cell influx during inflammation determines both the successfulness of pathogen elimination and the level of resulting tissue damage. Zebrafish embryos provide excellent opportunities to visualize the inflammatory response. Neutrophil granules may be stained with Sudan black, and variation in neutrophil counts may be used to monitor the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…A similar percentage of carvacrol was also present in Th.ca EO from Greece, while in the Iranian Sa.mo EO it showed a lower amount (25.9 %) . The behavior of Th.vu EO was the same as that provided by doTERRA …”
Section: Resultsmentioning
confidence: 99%
“…A similar percentage of carvacrol was also present in Th.ca EO from Greece, while in the Iranian Sa.mo EO it showed a lower amount (25.9 %) . The behavior of Th.vu EO was the same as that provided by doTERRA …”
Section: Resultsmentioning
confidence: 99%
“…rerio embryos. Although essential oils are often considered to be safer, a similar experiment with the thyme essential oil showed that it was able to cause 100% of embryo mortality at the concentration of 0.05 mg/mL at 72 hours post fertilization (hpf) [96]. In our experiment, 100% mortality occurred when a 0.9 mg/mL concentration was used and it is possible to observe that the mortality observed for the embryos did not exceed 30% even using a concentration 4.5 times higher than the recommended for the limit test (S1B Fig).…”
Section: Discussionmentioning
confidence: 99%
“…By the way, Hoskonen et al [12] report the toxicity of clove EO, when used to control saprolegniosis during incubation of rainbow trout eggs. In vivo adverse biological effects, as well as a toxicity of thymol and carvacrol on zebrafish ( Danio rerio ) models, were recently reported by Ran et al [22] and Polednik et al [23]. For this reason, the administration of EOs obtained from Lamiaceae family, containing large amounts of phenols, although biologically effective, should be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%